Synthesis, Characterization, and Theoretical Study of Novel Charge-Transfer Complexes Derived from 3,4-Selenadiazobenzophenone - Haider Shanshool Mohammed; Nuha Hussain Al-Saadawy (Universitas Gadjah Mada, 2022)
In the current study, a direct method was used to synthesize a new series of charge-transfer complex compounds. Reaction of different quinones with 3,4-selenadiazo benzophenone in a 1:1 mole ratio by acetonitrile gave a unique charge-transfer complex compound in a good yield. All compounds were characterized by UV-Vis, FTIR, 1H-NMR, and 13C-NMR. The analysis findings agreed with the produced compound’s proposed chemical structures. The molecular structure of the produced charge-transfer complex compounds has been investigated using density functional theory. The basis set of 3–21G geometrical designs throughout the geometry optimization, HOMO surfaces, LUMO surfaces, and energy gap has been created. The acceptor and donor have also been studied by comparing the HOMO energies of the charge-transfer complexes. The lower case, electron affinity, ionization potential, electronegativity, and electrophilicity where the total energies of donor-acceptor system and geometric structures demonstrate this structure’s stability. Additionally, the donor-acceptor system has higher reactivity than other systems and larger average polarizability when compared to the donor and acceptor. The findings of this study enable us to choose the kind of bridge that will interact with the donor and acceptor to determine the physical characteristics of the donor-bridge-acceptor.